Economics as Seen by an Ethicist a Personalist Perspective - Wojciech Wojtyła (Przegląd Prawno-Ekonomiczny)
This paper is intended to reconstruct the personalist understanding of relations between person and economics. Beginning with the concept of economics as a science whose fundamental categories are the production, exchange and division of material goods and profit, and adopting the personalist perspective, the author explores the economic roots going deeper than income alone, defined in terms of financial gain. This reasoning seems particularly important as economics is extremely susceptible to unethical mechanisms leading to various forms of alienation.